GEOMETRIC SHAPE FOR IRRIGATION SEDIMENT TRAPS VORTEX SETTLING DESILTING BASIN (GEOMATE Journal, 2023)
Modern irrigation schemes are increasingly demand-based, which means that the crop water requirements determine the water flow in a canal. The sediment transport aspect is a significant factor in irrigation development as it determines to a large extent the sustainability of an irrigation scheme, particularly in the case of unlined canals in alluvial soils, and as a trigger in reducing the wet capacity of the irrigation canal. The conventional sediment traps with a rectangular shape, rapidly advancing development, are challenging to construct because they require adequate space. The Vortex Settling Desilting Basin (VSDB) has proposed to replace the rectangular shape with more effectiveness considering the more concise area, deposition rate and removal efficiency, and minimum human resources as an operator. The method uses numerical methods with Computational Fluid Dynamic (CFD) simulations by Ansys R.21 2020 Student to acquire a geometric shape approach, then laboratory experiments with a model scale 1:40 prototype to an undistorted 3D physical model. This study aims to develop a two-dimensional numerical model and the optimal regression equations for determining settling basin dimension and then simulate and compare the efficiency of the selected settling basins. The VSDB shape is slimmer at 42% than the rectangular shape by optimizing the slope orifice chamber. As a result, by comparing the performance of rectangular sediment traps with the apple-to-apple hydraulic parameters and sediment variables, the results obtained based on deposition performance increased from 69.12% to 84.90% and flushing performance by leaving the minimum sediment fraction increased from 53.33% to 87.90%.